1979
DOI: 10.1111/j.1399-0039.1979.tb00797.x
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Antigens of Black Americans

Abstract: Forty‐four unrelated North American Blacks and one Black family were tested for B‐cell specific antigens with 7th International Workshop antisera. DR specificities were clearly defined in this group, but were generally less frequent than those reported for Black Americans in the 7th Workshop report and were most similar in frequency to those reported for African Blacks. Five new B‐cell specificities (DuB40–43, 45) were identified. In contradistinction to Caucasians, Black Americans typed for HLA—D with homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
2
2
0
Order By: Relevance
“…The data on these sera should then be interpreted as providing indirect evidence of the existence of one or more, as yet undefined DR antigens which, in addition to DRwl and DRw2, are associated with this public determinant. Although different criteria were used for the definition of DRw in this Black panel, we observed that the frequencies of DRwl, DRw2, DRw3, DRw5, DRw6 and DRw7 were similar to those reported for North-American Blacks by Bodmer et al (1978), but higher than the data reported by Ward et al (1979). The frequencies of DRwl, DRw2, DRw3, DRw5, DRw6 and DRw7 in this Black cell panel fitted in a Hardy-Weinberg distribution suggesting that these DRw antigens are controlled by multiple alleles of a single gene.…”
Section: Hardy-weinberg Fit For Drw Antigenssupporting
confidence: 62%
See 2 more Smart Citations
“…The data on these sera should then be interpreted as providing indirect evidence of the existence of one or more, as yet undefined DR antigens which, in addition to DRwl and DRw2, are associated with this public determinant. Although different criteria were used for the definition of DRw in this Black panel, we observed that the frequencies of DRwl, DRw2, DRw3, DRw5, DRw6 and DRw7 were similar to those reported for North-American Blacks by Bodmer et al (1978), but higher than the data reported by Ward et al (1979). The frequencies of DRwl, DRw2, DRw3, DRw5, DRw6 and DRw7 in this Black cell panel fitted in a Hardy-Weinberg distribution suggesting that these DRw antigens are controlled by multiple alleles of a single gene.…”
Section: Hardy-weinberg Fit For Drw Antigenssupporting
confidence: 62%
“…It was not clear whether these sera detected an unidentified DR specificity associated with Bw45. Table 3 lists the gene frequencies of DRw in this Black donor panel compared with data reported at the Seventh International Workshop (Bodmer et al 1978, p. 67), and with techniques reported by Ward et al (1979). Our frequency data were similar to the Oxford data on North-American Blacks although different criteria for DRw definition were used.…”
Section: Definition Of Drw6supporting
confidence: 52%
See 1 more Smart Citation
“…Typing for HLA-DR1-7 was performed using prolonged incubation and a B lymphocyte enriched population prepared with a nylon wool column. Antigen frequencies of sarcoidosis patients were compared to data from previously published studies of normal North Carolina Blacks (Ward 1975, Ward et al 1979. All contingency tables were analyzed using either Fisher's exact test or Pearson's chi-square and reported P values are all two-tailed.…”
mentioning
confidence: 99%